Home Visiting Work: A Transdisciplinary Study. (July 2020) - Bräutigam, Barbara; Lüngen, Sarah; Müller, Matthias
Purpose: Home visiting (HV) work represents an expanding, extremely promising, and commonly practiced approach that can be seen in various areas of social work as well as health care. This report presents the results of the research study "'home treatment' (HT)—transdisciplinary research in HV work." Method: It is the first German study that has used qualitative and quantitative methods to collect data from different professions in respect to this topic. From the point of view of the professionals, the study underlines that HV work principally seems to be a good base for establishing a professional and confidential relationship. They attribute more sustainability and participation from the clients to home-based interventions than other forms of help. After a short introduction about the current situation of HV work, the research project will be explained and the qualitative and quantitative methods described. Results: The results of the "HT Questionnaire" will be presented in 10 sections and the qualitative results in a model for reflection based on three points of view and five main topics. Discussion: Finally, some ethical and safety aspects will be discussed.